Understanding the Spatial Patterns of Police Activity and Mental Health in a Canadian City - Hodgkinson, Tarah (Journal of contemporary criminal justice, 2019)
Mental health-related calls for service are increasing across Canadian communities. However, the spatial dynamics of these calls for service and their potential relationship with concentrations of crime has not been fully investigated in the Canadian context. The current study examines mental health and other calls for service in a medium-sized (approximate population of 250,000), midwestern Canadian city in the year 2014. Using kernel density analysis and a spatial point pattern test, the study explores the concentration and spatial patterns of mental health calls for service across the city. Findings indicate that mental health calls for service differ from other crime-related calls for service, except for violent crime. Possible explanations for this pattern and considerations for policy and policing are discussed.